Fostamatinib Inhibits Neutrophils Extracellular Traps Induced by COVID-19 Patient Plasma: A Potential Therapeutic - Strich, Jeffrey R (J Infect Dis, 2020)
Neutrophil extracellular traps (NETs) contribute to immunothrombosis and have been associated with mortality in coronavirus disease 2019 (COVID-19). We stimulated donor neutrophils with plasma from patients with COVID-19 and demonstrated that R406 can abrogate the release of NETs. These data provide evidence for how fostamatinib may mitigate neutrophil-associated mechanisms contributing to COVID-19 immunopathogenesis.